Genetic Diversity and Construction of Core Collection of Sterculia Germplasm (Bangladesh Journal of Botany, 2024)
Amplification of 107 Sterculia accessions with 12 ISSR primers resulted in 235 bands, the percentage of polymorphic sites was 100%, with the average number of effective alleles (Ne) of 1.2464, the average Nei’s gene diversity index (H) of 0.1556, the average Shannon's information index (I) of 0.2563, and the average polymorphism information content (PIC) of 0.8594, indicating that the collected 107 accessions had high genetic diversity. The genetic diversity was unevenly distributed among Sterculia samples collected from different provinces, and the highest value was observed in samples from Guangdong Province, followed by those from Yunnan Province, and the lowest was from Guangxi Province. The core collection construction of the 107 Sterculia accessions was carried out by using the SCR and LDSS methods, respectively, and the results showed that the LDSS method was more suitable for Sterculia germplasm. Different core collections were constructed based on sampling proportions of 35, 30, 25, 20 and 15%, respectively, the t-test and principal coordinates analysis results showed that the genetic diversity of the original germplasm can be fully represented at a sampling proportion of 30%.Bangladesh J. Bot. 53(2): 319-325, 2024 (June)